LASER BIOPHOTONICS : Photodynamic effect of radiation with the wavelength 405 nm on the cells of microorganisms sensitised by metalloporphyrin compounds. (30th June 2016) - Korchenova, M V; Tuchina, E S; Shvayko, V Y; Gulkhandanyan, A G; Zakoyan, A A; Kazaryan, R K; Gulkhandanyan, G V; Dzhagarov, B M; Tuchin, V V
Abstract: We have studied the photodynamic activity of photosensitisers based on metalloporphyrins. New metalloporphyrin compounds are synthesised and characterised, the quantum yields of the singlet oxygen formation are analysed. It is shown that when the photodynamic effect is implemented using the metalloporphyrins with Zn ions and butyl radical in the 3rd and 4th positions of the pyridine ring, the number of opportunistic bacteria, such as Staphylococcus aureus (antibiotic-sensitives and antibiotic-resistant strains), Staphylococcus simulans and Escherichia coli is efficiently reduced by 90% – 99%.